-
2FJ.RU

:

:

[+]

------T---T---T---T---T---T---T---T---T---T---T---T---T---T---T---T---T---

a p p p p 2 p3 p5 p p 7 p5 p4 p3 p5 p7 p11p2 p

0 6 4 3 2 3 4 6 6 4 3 2 3 4 6

+-----+---+---+---+---+---+---+---+---+---+---+---+---+---+---+---+---+---+

1 ?2 ?3 ?3?2 1 -1 -?2-?3 -?3-?2-1

sin a 0 2 2 2 1 2 2 2 0 2 2 2 -1 2 2 2 0

+-----+---+---+---+---+---+---+---+---+---+---+---+---+---+---+---+---+---+

?3 ?2 1 -1 -?2-?3 -?3-?2-1 1 ?2 ?3

cos a 1 2 2 2 0 2 2 2 -1 2 2 2 0 2 2 2 1

+-----+---+---+---+---+---+---+---+---+---+---+---+---+---+---+---+---+---+

1 -1 1 -1

tg a 0 ?3 1 ?3 - -?3-1 ?3 0 ?3 1 ?3 - -?3-1 ?3 0

+-----+---+---+---+---+---+---+---+---+---+---+---+---+---+---+---+---+---+

1 -1 1 -1

ctg a - ?3 1 ?3 0 ?3-1 -?3 - ?3 1 ?3 0 ?3 -1 -?3 -

L-----+---+---+---+---+---+---+---+---+---+---+---+---+---+---+---+---+----

.

-----\------T-----------T------------T-----------T-------------T

\ A 0 1 -1 1

\ 2

-------\--------------------------+-----------+-------------+

cos x = a p p

x= 2 + p*n x = 2 p*n x = p + p*nx= + 3 +2p*n

----------------------------------+-----------+-------------+

p p k p

sin x = a x = p*n x = 2 +2 p*nx= -2 +2p*nx=(-1) *6+2pn

+----------------------------------+-----------+-------------+

p p 1

tg x = a x = 2 p*n x = 4 + p*n x= -4 +p*n x=arccos 2+pn

+-----------+-----------+------------+-----------+-------------+

p p 3p 1

ctg x = a x = 2 + p*nx = 4 + p*n x=-4 + p*n x=arccos2 +pn

L-----------+-----------+------------+-----------+--------------

---- ---T---------------T------------

sin2a + cos2a=1 sina a -

tga * ctga=1 tga=cosa b -

1 cosa f -

1+ctg2a=sin2a ctga=sina p -

1 y -

1+tg2a=cos2a x -

+------------------+---------------+------------+

sin2a=2sina*cosa

cos(a-b)=cosa*cosb+sina*sinb

cos2a=cos2a-sin2a=cos(a+b)=cosa*cosb-sina*sinb

=1-2sin2a=2cos2a-1sin(a-b)=sina*cosb-cosa*sinb

sin(a+b)=sina*cosb+cosa*sinb

+------------------+----------------------------+

2*tga tga+tgb

tg2a=1-tg2a tg(a+b)=1-tga*tgb

a sina 1-cosa

tg2 =1+cosa=sina tga-tgb

tg(a-b)=1+tga*tgb

+------------------+----------T-----------------+

a+b a+b a 1-cosa

cosa+cosb = 2cos 2 * cos 2 sin2 2 = 2

a+b a-b

cosa-cosb = -2sin 2 * sin 2 a 1+cosa

a+b a-b cos2 2 = 2

sina+sinb = 2sin 2 * cos 2

a-b a+b

sina-sinb = 2sin 2 * cos 2

L-----------------------------+------------------

 
 

:


       

   
       

.